Social Media’s Influence on Gendered Interpersonal Communication: Insights from Jordan - Aseel Zibin; Yara Al-Sabatin; Abdel Rahman Mitib Altakhaineh (Journalism and Media, 2025)
This study aims to examine the impact of social media on interpersonal communication patterns in Jordan and determine whether there are gender differences. Through adopting a mixed-methods approach, quantitative data were collected using a structured questionnaire from a sample of 50 Facebook users in Jordan chosen based on a self-selection method, comprising 24 men and 26 women, and two semi-structured focus group discussions were conducted with randomly selected 10 men and 10 women. The quantitative analysis showed that there were statistically significant differences between genders in terms of nonverbal communication and communication roles. However, no significant differences were found in verbal communication, listening, feedback, context, communication channels, and conflict resolution. The qualitative data provided further insight into the findings, demonstrating how cultural and societal norms, particularly those related to gender roles, influence interactions on social media. The participants expressed a range of perspectives on how social media impacts their communication, with many noting changes in communication dynamics due to increased exposure to global influences. In line with Genderlect Theory this study highlights the role of gender, demonstrating that while traditional gender-based communication styles endure, they are progressively shaped by the dynamic and evolving nature of digital interactions.